Administración del sistema colombiano de pensiones obligatorias (2010)
This paper attempts to analyze the effectiveness of the mechanism of multifunds recently entered the country through financial reform (Law 1328 of 2009) as a tool contributing to greater capitalization of the pension system in the form of individual savings, which would benefit the members of the when seeking access to the recognition of pension provision. This consideration given to the shortcomings concerning the above scheme, since the member with their savings in their individual account, but not enough to cover forty percent (40%) of historical average of their income when the pension access, what denoting non-viability of the pension system as regards the recognition of a pension to keep at least the purchasing power of the member, at the time of retirement. The scheme multifund, is presented as an alternative to deepen the capital market and simultaneously To prone to streamline the administration of the pension reserves by financial companies responsible for that task, in order to anchor the necessary resources to secure more capital at the time to recognize the pension obligation, thus appealing to a diversified investment portfolio resources exposed to different levels of risk depending on the profile and age of the contributor